(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The history of witchcraft and its relentless persecution unveils an eerie reflection of humanitys darkest insecuritiesa theater where fear choreographs brutality, and superstition scripts social control. Across centuries and continents, from the fiery witch trials of medieval Europe to the silent cries echoing through rural India, witchcraft accusations have served as the alibi for societal discord, gender-based violence, and systemic oppression. It is a narrative as old as time, and yet, as contemporary as tomorrows headlines, where the word "witch" is less a label and more a cultural dagger, striking down the vulnerable under the guise of morality and tradition. This study embarks on an ambitious exploration of the witch-hunting phenomenon, tracing its spectral presence from historical accounts to its chilling manifestations in todays world. The work argues that witchhunting is not merely a relic of an unenlightened past but a continuing saga, underscored by enduring societal fears and entrenched patriarchy. It deconstructs the macabre dance of superstition and gender politics, where folklore casts women as harbingers of misfortune and witchcraft becomes the pretext for violence. The analysis homes in on India, where systemic failures and cultural inertia perpetuate the scourge of witch accusations, particularly targeting women on the fringes of societywidows, economically disadvantaged, or those who dare to challenge patriarchal norms.